Of the people, by the people : a new history of democracy - Roger Osborne (London : Bodley Head, 2011)
Democracy is the worst form of government, except for all those other forms that have been tried from time to time'. Churchill had more reason than most to rue the power of democracy, having been thrown out of office after leading Britain to victory in 1945. Democracy, when viewed from above, has always been a fickle master; from below it is a powerful but fragile friend. Most books on democracy focus on political